2018
DOI: 10.1007/s10964-018-0823-8
|View full text |Cite
|
Sign up to set email alerts
|

Organized Activity Involvement among Urban Youth: Understanding Family- and Neighborhood- Level Characteristics as Predictors of Involvement

Abstract: Research examining factors that predict youth's involvement in organized activities is very limited, despite associations with positive outcomes. Using data from 1043 youth (49% female; 46.4% Hispanic, 35.4% African American, 14.0% Caucasian, and 4.2% other) from the Project on Human Development in Chicago Neighborhoods, this study examined how characteristics of parents (supervision, warmth) and neighborhoods (perceived neighborhood safety and collective efficacy) predict patterns of adolescents' involvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
2
0
2
Order By: Relevance
“…In a group of Palestinian adolescents, exposure to community violence was associated with less parental monitoring and knowledge of children's whereabouts (Darawshy & Haj-Yahia, 2018). However, other studies have not found support in either direction (Anderson et al, 2018;Ball et al, 2007;Hong et al, 2018).…”
Section: Behavior Controlmentioning
confidence: 89%
“…In a group of Palestinian adolescents, exposure to community violence was associated with less parental monitoring and knowledge of children's whereabouts (Darawshy & Haj-Yahia, 2018). However, other studies have not found support in either direction (Anderson et al, 2018;Ball et al, 2007;Hong et al, 2018).…”
Section: Behavior Controlmentioning
confidence: 89%
“…Two notable aspects of parenting that have been consistently linked to delinquency are monitoring and warmth. Parental warmth refers to a parent−child relationship characterized by healthy attachment that generates positive emotions and strengthens the parent−child bond (e.g., Anderson et al, 2018; Fletcher et al, 2000; Kerr & Stattin, 2003). Parental monitoring refers to the degree that parents supervise their children’s behavior and the level of knowledge they have regarding their child’s activities, whereabouts, and acquaintances.…”
Section: Do Peer Effects Mediate the Association Between Parenting An...mentioning
confidence: 99%
“…Recent work has shown the disparity in participation rates across socioeconomic status has widened over the previous 25 years, further demonstrating the sustained inequality of access to organized activities (Meier, Hartmann, & Larson, 2018). It is therefore apparent that participation in organized activities reflects an interplay between adolescents' motivation to engage and contextual constraints evident in the community (Anderson, Bohnert, & Governale, 2018;Fredricks et al, 2002;Mahoney et al, 2005). As such, socioeconomic disadvantage could not only limit initial access, but also set in motion a process of quitting an activity, irrespective of the internal motivations and desires of the activity participant.…”
Section: Organized Activitiesmentioning
confidence: 99%